(untitled) (World Bulletin of Management and Law, 2023)
In this article, the 7th grade course “natural geography of materials and oceans” is mentioned, giving several methodological recommendations on the use of the “dating” training on the topic of the nature zones of Eurasia. As a result of the application of this method, the school provides a special service for strengthening both theoretical and practical knowledge of students, in the development of such characteristics as creativity, traceability